The Effectiveness of Dragon Fruit Consumption For Increasing Haemoglobin Levels In Pregnancy Women With Light Anemia Symptoms - Miratu Megasari; Risa Pitriani (Science Midwifery, 2021)
Anemia in pregnant women often occurs due to changes in the cardiovascular system that cause haemodilution, resulting in reduced oxygen levels in the blood. A solution to prevent anemia in pregnant women is to consume fruits that contain high iron and vitamin C such as dragon fruit which is needed to synthesize haemoglobin. From a preliminary study at the Pramuka Primary clinic, 8 out of 15 pregnant women had Hb levels <11.5 g/dl. Based on the author's experience, there are still pregnant women who do not consume blood-boosting tablets because the side effects of these tablets causing nausea, black stools. The population in this study were all pregnant women who were recorded at the Pratama Primary Clinic. The sample in this study was pregnant women in the first trimester who experienced anemia. The sampling technique used is accidental sampling. The method used in this study is a quasi-experimental. The type of design in this study was in the form of a non-equivalent design (pretest and post-test). The results of this study showed that the average hemoglobin level of pregnant women before consuming dragon fruit was 9.17 gr%, while the average hemoglobin level of pregnant women after consuming dragon fruits was 10.15gr%. The results of the statistical test value of 0.001 means that there is a significant difference between Hb levels before and after consuming dragon fruits.